Computational Fluid Dynamics-Based Hydrodynamics Studies in Packed Bed Columns: Current Status and Future Directions - Malang, J.; Kumar, P.; Saptoro, Agus (2015)
A careful review of the literature reveals that extensive research has been done on the hydrodynamics in packed bed columns using turbulence models. It can be noted that the choice of turbulence model is influenced by the number of phases, type of fluid, Reynolds number range and the type of packing. Thus, comparison of turbulence models for the selection of a suitable model assumes great importance for the better prediction of flow pattern. This is due to the fact that poor prediction of the flow pattern can lead to a limited heat and mass transfer model as the rate of transfer processes in packed bed is governed by the hydrodynamics of the packed bed. The aim of this paper is to give a review of the computational fluid dynamics (CFD)-based hydrodynamics studies of packed bed columns with the primary interest of studying pressure drop and drag coefficient in packed beds. From the literature survey in Science Direct database, more than 48,000 papers related to packed bed columns have been published with more than 3,000 papers focused on the hydrodynamic studies of the bed to date. Unfortunately, there are only a few studies reported on the hydrodynamics of packed columns under supercritical fluid condition. Therefore, it is imperative that the future work has to focus on the hydrodynamics of supercritical packed column and particularly on the selection of suitable turbulence model.